FORMATION OF THE KABARDIAN NATIONAL MOVEMENT (1985-1991) - KUSHKHABIEV, A.V. (Kavkazologiya, 2020)
The article presents an analysis of the formation of the Kabardian national movement. It is shown that the Kabardian national movement, which formed during the perestroika period (1985-1991) around the club «Ashamaz», had a significant impact on the socio-political situation in Kabardino-Balkaria. Representatives of the Kabardian national democratic community participated in the creation and activities of some regional public associations. The main goals and objectives of the public associations included in the Kabardian national movement were to solve the problems of ethnocultural development and to promote democratic transformations. Since October 1989, the activities of public organizations of the Kabardian national movement have been focused on resolving political questions, primarily on reforming the national-state structure of the republic. Disagreements on this issue caused the aggravation of relations between the Kabardian and Balkarian national movements. During the coup in August 1990, the Democratic Kabardino-Balkaria movement, formed by the Kabardian and Balkarian national movements and parliamentary groups Radical Reform and the Communists for Democracy, opposed the republic’s leadership, accusing it of supporting the State Emergency Committee. But the leadership of the republic managed to maintain its position and establish the post of President of the KBSSR. After the decision by the Balkarian national movement to create a separate republic, the Kabardian national movement began to prepare a congress with the aim of proclaiming the Kabardian Republic. But the leadership of the KBSSR took measures to preserve the unity of the republic – created the «Movement for the Preservation of Unity of Kabardino-Balkaria» and held the election of the President of Kabardino-Balkaria (12.22.1991), despite their boycott by the predominant part of the Balkarian and Russian population of the republic.